2012
DOI: 10.5296/ije.v4i4.2269
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Increased Workloads on Online Instruction

Abstract: The workload increase for California State University instructors has been significant, as has been the reduction in resources and support. Online instructors are facing the same set of circumstances as their campus-based peers, yet the impact of said circumstances has not been fully realized. Still most instructors want to do be effective in their teaching practices and will do what it takes to facilitate student learning. This paper examines the impact of budget cuts on online instructors, including increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…Few students are capable of complex learning without focused facilitation from knowledgeable experts. Arbaugh & Benbunan-Fich, 2005;Bain, 2004;Benbunan-Fich et al, 2005;Bozkurt et al, 2015;Chu, Zhang, Chen, Chan, Lee, Zou, & Lau, 2017;Curriculum Committee, 2012;El Tantawi, Abdelsalem, Mourady, & Elrifae, 2015;Holtslander, Racine, Furniss, Burles, & Turner, 2012;Holzweiss et al, 2014;Jones, 2015;Kim, 2013;Legg, Adelman, & Levitt, 2009;Mandel & Sussmuth, 2011;Maringe & Sing, 2014;Picciano, 2017;Ravenna, 2012;Schellens & Valcke, 2006;Schwartz, 2014;Taft et al, 2011;Williams, Jaramillo, & Pesko, 2015 Bloom's taxonomy: A classic in education theory, categories of learning level align in a pyramid, from simple/concrete (lower levels) to complex/abstract (higher levels). Each category contains subcategories.…”
Section: Elaborated Description Of Three Learning Theories-objectivismentioning
confidence: 99%
See 3 more Smart Citations
“…Few students are capable of complex learning without focused facilitation from knowledgeable experts. Arbaugh & Benbunan-Fich, 2005;Bain, 2004;Benbunan-Fich et al, 2005;Bozkurt et al, 2015;Chu, Zhang, Chen, Chan, Lee, Zou, & Lau, 2017;Curriculum Committee, 2012;El Tantawi, Abdelsalem, Mourady, & Elrifae, 2015;Holtslander, Racine, Furniss, Burles, & Turner, 2012;Holzweiss et al, 2014;Jones, 2015;Kim, 2013;Legg, Adelman, & Levitt, 2009;Mandel & Sussmuth, 2011;Maringe & Sing, 2014;Picciano, 2017;Ravenna, 2012;Schellens & Valcke, 2006;Schwartz, 2014;Taft et al, 2011;Williams, Jaramillo, & Pesko, 2015 Bloom's taxonomy: A classic in education theory, categories of learning level align in a pyramid, from simple/concrete (lower levels) to complex/abstract (higher levels). Each category contains subcategories.…”
Section: Elaborated Description Of Three Learning Theories-objectivismentioning
confidence: 99%
“…Evaluation: forming judgments about the value of materials and methods for specific purposes The revised taxonomy (2001) added Level 7: 7. Creation: generating, developing, designing, planning, or producing Armstrong, n.d.;Bloom et al, 1956;Holzweiss et al, 2014;Meyer, 2006;Ravenna, 2012;Taft et al, 2011 Theory Description Sources Use of the CoI model enhances student learning and satisfaction. Numerous studies have confirmed the value of the CoI.…”
Section: Elaborated Description Of Three Learning Theories-objectivismentioning
confidence: 99%
See 2 more Smart Citations
“…This is particularly important in graduate level education, where expectations of academic rigor and achievement are greater (Bowden, 2012). It is evident that the level of presence and degree of visible involvement demonstrated by the instructor is dependent upon the teaching strategy and personal preferences of the instructor (Ravenna, 2012). However, it is also evident that the level of teaching presence can dramatically influence the quality of facilitation that leads to successful learning in asynchronous environments (Costley, 2015;Hung & Chou, 2015;Rovai, 2007).…”
Section: The Nature Of Teaching Presencementioning
confidence: 99%